Comparative Cytogenetic Characterization of Grammatophyllum martae, Dendrobium violaceoflavens, and Dendrobium Tiara Beauty × D. Graty - Sri Hartati; Fitria Roviqowati; Yuni Tuwenti (Journal of Biodiversity and Biotechnology, 2026)
Orchids are among the most popular ornamental plants widely favored by the public. Plant breeders continuously strive to improve the quantity, quality, and cytological characteristics of orchids to support successful breeding programs. This study aimed to determine the cytological characteristics of Grammatophyllum martae, Dendrobium violaceoflavens, and the hybrid D. Tiara Beauty × D. Graty, including chromosome number, chromosome size, chromosome shape, karyotype, and chromosome asymmetry index. The research was conducted at the Plant Breeding Laboratory, Faculty of Agriculture, Universitas Sebelas Maret, from July to August 2025. The number, size, shape, and karyotype pattern of chromosomes were analyzed descriptively. The results showed that G. martae, D. violaceoflavens, and the hybrid D. Tiara Beauty × D. Graty have the same chromosome number, 2n = 38, composed of metacentric chromosomes. The chromosomes of G. martae had a total arm length of 1.10 ± 0.28 µm, D. violaceoflavens 1.48 ± 0.40 µm, and the hybrid D. Tiara Beauty × D. Graty 1.30 ± 0.36 µm. The intrachromosomal (A1) and interchromosomal (A2) asymmetry indices of the three observed orchids were low, indicating that their karyotypes tend to be symmetrical, as they are composed of metacentric chromosomes with minimal size variation.